Interaction effect of prenatal and postnatal exposure to ambient air pollution and temperature on childhood asthma - Chan Lu; Yinping Zhang; Baizhan Li; Zhuohui Zhao; Chen Huang; Xin Zhang; Hua Qian; Juan Wang; Wei Liu; Yuexia Sun; Dan Norbäck; Qihong Deng (Environment International, 2022)
Background: Although mounting evidence has associated air pollution and environmental temperature with children’s health problems, it is unclear whether there is an interaction between these factors on childhood asthma. Objectives: To explore the effects of temperature-pollution interactions during pre- and post-natal periods on asthma among pre-schoolers. Methods: A retrospective cohort study of 39,782 pre-schoolers was performed during 2010–2012, in seven cities in China. Exposure to three temperature indicators (TI) and three critical ambient air pollutants, including particulate matter with aerodynamic diameter ≤ 10 μm (PM10), sulfur dioxide (SO2) and nitrogen dioxide (NO2) as proxies of industrial and vehicular air pollution, was estimated by an inverse distance weighted (IDW) method. Two-level logistical regression analysis was used to examine the association between both pre- and post-natal exposure and childhood asthma in terms of odds ratio (OR) and 95 % confidence interval (CI). Results: Asthma prevalence in pre-schoolers at age of 3–6 years (6.9 %) was significantly associated with traffic-related air pollutant (NO2) exposure, with ORs (95 % CI) of 1.17 (1.06, 1.28), 1.19 (1.05–1.34) and 1.16 (1.03–1.31) for an IQR increase in NO2 exposure during lifetime, pregnancy, and entire postnatal period respectively. Furthermore, childhood asthma was positively associated with exposure to increased temperature during lifetime, pregnancy, and entire postnatal period with ORs (95 % CI) = 1.89 (1.66, 2.16), 1.47 (1.34, 1.61), and 1.15 (1.11, 1.18) respectively, while was negatively associated with decreased temperatures. Childhood asthma was positively related with exposure to extreme heat days (EHD) during postnatal period particularly in first year of life respectively with ORs (95 % CI) = 1.23 (1.04, 1.46) and 1.26 (1.07, 1.47), but was not related with extreme cold days (ECD) exposure. A combination of high air pollutant levels and high temperatures significantly increased the risk of asthma during both pre- and post-natal periods. Strikingly, we found a significantly positive interaction of temperature and PM10 or SO2 on asthma risk among boys and younger children. Conclusions: Prenatal and postnatal exposure to ambient air pollution and high temperatures are independently and jointly associated with asthma risk in early childhood.